İmagining Macedonia in the age of empire : state policies, networks and violence (1878-1912) - Ljuljanovic, Denis (My University, 2021)
Tezin odak noktasını, yerel komiteler, Balkan ülkeleri, Büyük Güçler ve Osmanlı Devletigibi farklı aktörleri içeren Makedonya Sorunu oluşturmaktadır. Bu aktörler 19. ve 20. yüzyılboyunca Osmanlı topraklarında Makedonya olarak bilinen üç vilayeti bölüşme amacıylamücadele etmişlerdir. Her bir Balkan devletinde entelektüeller ve devlet adamları, kendi büyükdevlet projelerine Makedonya’yı dâhil etmek için tartışmalı stratejiler geliştirmişlerdir. Bubağlamda, çalışma adı geçen bu farklı aktörleri, Berlin Kongresi (1878) ile Balkan Savaşları(1912/ 13) arasındaki zaman diliminde incelemiştir. Tezde, Osmanlıca, Bulgarca, Makedonca,Sırpça ve Arnavutça kaynaklarından istifade edilmiştir. Buna ek olarak, İngilizce, Fransızca,Almanca, İtalyanca ve Rusça raporlar da incelenmiştir. Bu yolla, çalışmada MakedonyaSorunu, uluslararası ve bölgesel aktörler üzerinden tartışmaya açılmıştır. Yanı sıra, tezde etnikkimlik tartışmalarının ötesine geçilerek, yereldeki çok katmanlı faktörlerin etkisi ortayaçıkartılmıştır. Bu açıdan, tezin ana düşüncesini, olayların bölgesel ve uluslararası düzeydeanlamlandırılabilmesi için yerelin öneminin vurgulanması ve öne çıkartılması oluşturmaktadır.Diğer bir deyişle, çalışma ulus-devletin ve devlet adamlarının geliştirdiği meta anlatılara karşıçıkarak, yerel düzeye odaklanmayı ve bu düzeydeki aktörlerin iç içe geçmiş ve çok katmanlıyapısını incelemeyi vurgulamaktadır.

The thesis is focusing on the complexity of the Macedonian Question(s) at the turn to the 20thcentury, which entailed multiple aspects: various local committees, the Balkan countries, theGreat Powers, and the Ottomans. At that time, these actors imagined variously one part of theOttoman territories that was becoming popular under the name of Macedonia. Many states andintelligentsia developed contested strategies to include these Ottoman provinces as part of theirmeta-narratives and greater state projects. In this respect, the thesis aims to analyse thesevarious actors in the time framework between the Congress of Berlin (1878) and the BalkanWars (1912/ 13). By using different regional sources from the Ottoman, Bulgarian,Macedonian, Serbian and Albanian languages, and European reports in English, French,German, Italian and Russian, the scope of this work is to bring into discussion the multiplicitiesentailed at the international, regional and trans-regional levels. Apart from it, the thesisincludes local level as well, in order to avoid the use of ’monolithic ethno-national identities’as a given, and rather to reflect the complexity of events on the ground. At that time and eventoday, some politicians, statesmen and intellectuals tried to implement various nationalnarratives and worldviews according to the primordial ethnoreligious containers withoutreflecting that the imposed identification are ambiguous and problematic with the situation atthe local level. Nevertheless, the dissertation does not aim to discard such works (and picture)of the locals that help to deconstruct the meta-narratives produced by the policies of the nationstate(s).
Keywords: International relations; Macedonian; Makedonya Ottoman State; Osmanlı Devleti; Political science; Siyasal bilim; Uluslararası ilişkiler